2011
DOI: 10.1111/j.1365-2788.2011.01383.x
|View full text |Cite
|
Sign up to set email alerts
|

Perceived credibility and eyewitness testimony of children with intellectual disabilities

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent repository link Method:The current study explored the transcripts of child witnesses with ID, relative to those of typically developing (TD) age-matched children, and assessed how mock jurors perceived these transcripts in the absence of knowledge of group (ID or TD) membership. A further aim of this research was to determine whether perceptions of credibility were associated with l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
31
1
10

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 22 publications
(29 reference statements)
1
31
1
10
Order By: Relevance
“…This is reflected in some clichés about persons with intellectual disability that suggest they would not be capable of making up complex lies and, therefore, would be more believable (Bottoms, Nysse-Carris, Harris, & Tyda, 2003). These clichés carry a negative charge, however, that results in persons with ID being viewed as witnesses who are less credible and less capable of giving valid testimony (Henry, Ridley, Perry, & Crane, 2011;Peled, Iarocci, & Connolly, 2004;Sabsey & Doe, 1991;Stobbs & Kebbell, 2003;Tharinger, Horton, & Millea, 1990;Valenti-Hein & Schwartz, 1993), which makes persons with ID more vulnerable to crimes (González, Cendra, & Manzanero, 2013). Peled et al (2004) explored the perceived credibility of young persons with ID who were required to give testimony in a legal setting.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…This is reflected in some clichés about persons with intellectual disability that suggest they would not be capable of making up complex lies and, therefore, would be more believable (Bottoms, Nysse-Carris, Harris, & Tyda, 2003). These clichés carry a negative charge, however, that results in persons with ID being viewed as witnesses who are less credible and less capable of giving valid testimony (Henry, Ridley, Perry, & Crane, 2011;Peled, Iarocci, & Connolly, 2004;Sabsey & Doe, 1991;Stobbs & Kebbell, 2003;Tharinger, Horton, & Millea, 1990;Valenti-Hein & Schwartz, 1993), which makes persons with ID more vulnerable to crimes (González, Cendra, & Manzanero, 2013). Peled et al (2004) explored the perceived credibility of young persons with ID who were required to give testimony in a legal setting.…”
Section: Introductionmentioning
confidence: 98%
“…When subsequently questioned about the credibility of the testimonies, they stated that those testimonies given by a person with ID were considered less credible. Henry et al (2011) evaluated the credibility of children with ID and of developmentally nor-mal children and found that the former, because they gave fewer details, were less credible than the latter. They found no correlation between the credibility evaluations and either mental age or anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…Children (and adults) with intellectual difficulties are vulnerable to maltreatment, but their allegations are less likely to progress through the legal system. This may be due, in part, to investigators’, prosecutors’, and jurors’ doubts about the ability of children with intellectual disabilities (CWIDs) to provide meaningful, detailed, and reliable information (e.g., Brown & Lewis, ; Henry, Ridley, et al ., ; Peled, Iarocci, & Connolly, ), and concern that prosecutions will therefore be unsuccessful (Aarons & Powell, ; Aarons, Powell, & Browne, ; Ericson, Perlman, & Isaacs, ; Nathanson & Platt, ). Developing evidence‐based recommendations for obtaining reliable information from CWID is important to facilitate their increased participation in legal proceedings (Henry, Bettaney, & Carney, ).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, there are factors that make it difficult to detect such acts of violence, intimidation and abuses, such as the lack of adapted tools, the usual communication model used by authorities (police, educators, health workers, etc.). Disability, and the credibility of the testimonies of people with Intellectual Disabilities, which is usually lower than that of persons without Intellectual Disability (Henry, Ridley, Perry and Crane, 2011;Peled, Iarocci and Connolly, 2004).…”
Section: Introductionmentioning
confidence: 99%